Iptek bagi Masyarakat Kelurahan Lere dalam Pengembangan Usaha Berbahan Baku Lamale (Penaeus sp.) - Wendy Alexander Tanod; Anita Treisya Aristawati; Deddy Wahyudi; Yeldi S Adel (Institut Pertanian Bogor, 2019)
Bahari Jaya 2 and Sehati are partner fishermen groups located in Lere urban village, West Palu District, Palu, Central Sulawesi. In general, the catches from the two partner fishing groups are small shrimp (Penaeus sp.), with local names lamale. The purpose of IbM activities is to improve the skills and knowledge of members of the Bahari Jaya 2 and Sehati fishing group, to be able to run a processed business made from raw shrimp lamale. The projects carried out from April to November 2015. The method consists of 3 stages: 1) The stage of problem determination; 2) Stage presentation, negotiation and programming; and 3) Facilitation and mentoring of partners. The success indicator of this project; namely the two partner groups able to sustainably run a processing business. The results achieved by the two partner groups, i.e., 1) Partners can process lamale into noodles and nuggets, 2) Partners know business prospects for lamale noodle and nuggets, 3) Partners know quality control, quality management and sanitation in processing business, 4) Partners know the nutritional composition of the lamale noodle and nuggets, 5) Both groups of partners can manage profit-oriented sales businesses.